Administration of Mung Bean Extract (Phaseolus radiatus) in Increasing Hb and Ferritin Level and Decreasing Malondyaldehide (MDA) Level in Anaemic Rats - Wijayanti, Heni; Nasihun, Taufiqurrachman; Hussaana, Atina (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2017)
BACKGROUND: Mung bean, not only contains protein, carbohydrates, and fats, but also contains iron and vitamin C which are proven to overcome anemia in pregnant woman. High iron levels are potential to increase ROS production through fenton reaction.OBJECTIVE: to prove the administration of mungbean can increase Hb and ferritin levels and decreasing malondihaldehyde (MDA) in anaemic rats.METHODS: This research uses Post Test Only Control Group Design. A total of 25 anaemic rats were divided into 5 groups: normal group (Nor-G);negative control group (Neg-G), were given low Fe diet; and treatment group with low Fe and mung bean extract at dose of 0,18g/200g/days (GP-0,18), 0,36g/200g/days (GP-0.36), dan 0,72g/200g/days (GP-0.72). Low Fe diet and mung bean extract were administered for 14 days. Hb levels were measured using Sahli method, ferritine level using Immulite Ferritine Kit, and MDA were measured using TBA.RESULTS: Compare to Nor-G and Neg-G, levels of ferritin and Hb on groups with mung bean extract 0,18g (75.56), 0,36g (90.98) and 0,72g (95.87) were significantly higher (p < 0.05). While MDA levels on groups with mung bean 0,18g (4.646), 0,36g (3.396) and 0,72g (1.92) were significantly lower than on Nor-G and Neg-G groups (p < 0.05).CONCLUSION: The administration of mung bean extract can increase Hb and ferritin, also lower MDA level on anaemic rats.